Building character : the art and science of casting - Cook, Amy, 1970- (University of Michigan Press, 2018)
What can we learn about how we understand each other and ourselves by examining the casting we find on stage and film--the casting we find perfect and the casting we find wrong? Building Character examines how the process of "casting" an actor in a part creates a character and how this can be usefully understood through deploying theories from the cognitive sciences. A casting director may match the perceived qualities of an actor with the perceived qualities of the character, but the combination is also synergistic; casting a character creates qualities. While casting directors do this professionally, all of us do this when we make sense of the people around us. This book argues that we build the characters of others from a sea of stimuli and that the process of watching actors take on roles improves our ability to "cast" those roles in our daily lives. Amy Cook examines the visible celebrity casting, such as Robert Downey Jr. as Ironman or Judi Dench as Bond's M, the political casting of one candidate as "presidential" and another as "weak," the miscasting of racial profiling and sexual assault, and the counter casting that results when actors and characters are not where or who we expect.